tangentes raaklijnen tangents. - de Zegher, Catherine; De Smet, Johan; Van Den Abeele, Lieven (Gent : Museum voor Schone Kunsten, 2016)
Dekyndt, Edith ; Gaisumov, Aslan ; Grzymala, Monika ; Knowles, Tim ; Laet, Maria ; Sze, Sarah ; Vermeersch, Pieter ; Wlodarczak, Gosia ; Wolseley, John
raaklijnen, Museum voor Schone Kunsten Gent, 10.10.15-05.03.16
boek